Вплив філософських та лінгвістичних концепцій на становлення багатомовної освіти школярів у країнах Європи - Оксана Першукова (Pavlo Tychyna Uman State Pedagogical University, 2013)
Статтю присвячено аналізу впливу основних напрямів філософських та лінгвістичних досліджень на становлення багатомовної освіти європейських школярів. Визначено, що він полягає у значному розширенні уявлень про людське суспільство та особистість, переосмисленні ролі мови та культури в суспільстві, усвідомленні потреб збереження мовного багатства, зміні мети та підходів до навчання та викладання мов. Зроблено висновок про те, що розвиток багатомовної освіти у країнах Європи є закономірною відповіддю на виклики сучасності. Статья посвящена анализу влияния основных философских и лингвистических направлений исследований на становление многоязычного образования школьников в странах Европы. Определено, что оно состоит в расширении представлений о человеческом обществе и личности, переосмысливании роли языка и культуры в обществе, осознании потребностей в сохранении языкового богатства, изменению цели и подходов и изучению и преподаванию языков. Сделан вывод о том, что развитие плюрилингвального образования в странах Европы - это закономерный ответ на вызовы современности The article deals with the influence of the main philosophical and linguistic theories of 20th and early 21st centuries significant for multilingual education formation. The main аnalyzed philosophical theories are pragmatism (Ch. Peirceе, W .James, F. Schiller, E. Cassirer, J. Dewey), constructivism (I. Kant, A. Schopenhauer), existentialism (G. Marcel, M. Heidegger, G. Kneller, V. Morris, M. James), modernism (J. Ortega y Gasset, J. Habermas), rationalism (B. Skinner, J. Searle), poststructuralism (D. Hume, F. Nietzsche, J.-F. Lyotard ), postmodernism (D. Hume, F. Nietzsche, M. Foucault, J. Baudrillard, A. Toynbee) and deconstructivism (J. Derridа, G. Deleuze, P.-F. Guattari, J. Kristeva). As shown in the present paper the development of knowledge in philosophy was tightly connected with new directions in linguistic investigations aimed on the nature of language and ties of language and thought understanding, the ways of plurilingualism forming and multilingualism saving. The development of these theories originated the development of linguistic conceptions, such as linguistic structuralism (F. de Saussure), generativism (N. Chomsky) and pragmatism (D. Hymes). The intensive development of philosophical theories and linguistic conceptions promoted new awareness of: the uniqueness of man as a spiritual being; inability of knowledge and skills mechanical transfer in the educational process; tight connections of language and thinking; perception of language as a mean of socialization, the basis of human relations as well as social structure; the existence of different points of view on the same event or phenomena and other. New knowledge actualized the essential changing in educational needs: careful attention to personal needs in education including language learning needs; attention not to single but widespread processes; critical stocktaking all existing universal laws; tolerant attitude forming to different cultural and groups peculiarities. In the second part of 20th century on the background of globalization the needs of plurilingualism and interculturality of European citizens were especially actualized, so the task to satisfy these needs was given to the multilingual (plurilingual) education. This education provides permanent rising of level of competence in some languages, forms the ability to use different languages as a mean of education. It improves understanding of social and cultural value of any language and necessity to preserve all linguistic diversity and cultural heritage.